A companion to African American literature - Gene Andrew Jarrett ([Place of publication not identifed] : Blackwell Publishers, 2010)
It studies the canons and traditions of African American literature, even as it unsettles their major assumptions and representations. On the other hand, this collection of essays, written by todays preeminent and rising scholars, examiners most of the well known texts, contexts, genres forms, themes, authors and interpretations of the literature authored by the African dispora in America.
Part I: The Literatures of Africa, Middle Passage, Slavery, and Freedom: The Early and Antebellum Periods, c.1750-1865 -- Part II: New Negro Aesthetics, Culture, and Politics: The Modern Period, 1865-c.1940 -- Part III: Reforming the Canon, Tradition, and Criticism of African American Literature: The Contemporary Period, c.1940-Present .
Includes bibliographical references and index.
Keywords: AFRICAN AMERICAN LITERATURE